Development of science-industry relationships in the context of knowledge creation. - Pohulak-Żołędowska, Elżbieta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
Nowadays the ability to innovate is the key factor in creating the innovative firm (in the micro-scale) or innovative economy (in a wider prospect). The important part of innovation system are universities where well-educated and well-skilled personnel, armed with the appropriate knowledge, competencies and equipment of academic research centres has the opportunity to discover new phenomena, and turn them into innovations. Lucrative relations of science and industry caused the emergence of new science types. These are post-academic and industrial sciences. The results of scientific research conducted within the post-academic or industrial science are company-dedicated solutions or inventions, which may be used after prior commercialization. The desired effect of cooperation between university and industry are commercialized effects of scientific research. There are various methods of university-industry cooperation. The goal of the article is to show the development and changes of university-industry relations on selected literature and empirical examples
Argumenta Oeconomica, 2011, Nr 1 (26), s. 43-56
Keywords: knowledge based economy; knowledge production; academic science; post-academic science; industrial science; innovation; gospodarka oparta na wiedzy; innowacje; wiedza